Co je co není informovaný souhlas - Sucharda, I (Casopis lekaru ceskych, 2002)
Coequalitisation of the relation between the physician and his patient, which respects the professional dominancy of the first one, has promoted the full guidance before any serious diagnostic or therapeutic intervention. Patient has the right to be informed of his health status and of the therapeutic plan. He has also the right to refuse such information. Only after the full information, the patients can express his approval with the plan for therapy. Before any intervention, the patient's approval is necessary; exceptional are only by the law implicated situations. To get the lawful and therefore the qualified or informed approval, the patient should be able to accept the information, to consider its significance, to make decision, and the express his will. Incapable of doing that is not only the person with permanently decreased ability to resolve, but also those who are not able to accept the information because of language problem and those, whose psychical state is influenced by the actual state of the disease, therapy etc. For a child, the person who has the right to be informed and to give the consent is his protector (usually his parent), however, within the limits of his comprehension an older child has also the right to express his opinion. For the common treatment the written form of approval is not necessary, it is enough to get the oral consent. For intervention of a higher significance and risks, the written form is recommended. It should be connected with a possibility to discuss and get explained any questions. The information should include not only what is to be done, but also how it will be done and what are the benefits of the treatment. It is essential to inform the patient also about the after-effects, side effects and possible complications, all that considering their significance and incidence. Information about the intervention and its risks does not limit the patient's right for compensatory damages, but it frequently improves communication and mutual collaboration between the patient and health care workers.
Keywords: Czech Republic; Legal Guardians; lidé; dítě; zákonný zástupce; Child; Humans; Mental Competency; Informed Consent; duševní schopnost; Česká republika; informovaný souhlas pacienta